Diffusion Channel System for Enhancing the Shelf Life of Fruits and Vegetables under Controlled/ Modified Atmosphere - Kandasamy, P.; Moitra, Ranabir; Mukherjee, Souti (International Journal of Bio-resource and Stress Management, 2023)
Fruits and vegetables generally have a short shelf life and begin to lose their freshness shortly after being plucked from the tree. This is because of the metabolic activities, which continue even after harvest. Respiration is one of the major metabolic activities, which involve the consumption of oxygen (O2) and evolution of carbon dioxide (CO2) along with water and energy in the form of heat. Controlling the respiration rate and other metabolic activities, minimize the physiological disorders such as rapid ripening, senescence, growth of mould, decay, degradation of chlorophyll and loss of vitamins. The respiration rate can be restricted by controlling temperature, relative humidity and altering the natural gas composition such as O2 and CO2. The modification process often tries to reduce the level of O2 and increase the level of CO2 initially and it changes dynamically depending on the produce and permeability of the packaging materials. Whereas in controlled atmosphere (CA) condition their levels are altered within air tight storage and maintain their optimum levels throughout the storage period suitable to the commodities. The desired gas composition in CA storage may be achieved either by static method where the product generates the atmosphere or by flushing method where a flowing gas stream purges the storage continuously, providing the storage atmosphere. In this paper, general aspects of the respiration process, important beneficial effects, detrimental effects, principles of gas diffusion, diffusion channel system and highlights of research related to CA storage with diffusion channel are presented.